Software development by integrating the integrated effort flow analysis and boothroyd - DFA - Ahmad Arif Syazni, Abd Rahman (2008)
This work proposed a framework to develop the software base on the integration of EFA and DFA by using Microsoft Visual Basic 6.0. This software can help the designer to design product easier compare manual designer. The expected output is software that able to aid the designer to create an opportunity to manufacturing of product with low assembly cost and labour time saving. Effort Flow Analysis uses an effort flow diagram to model a product as a connected set of nodes and links. The nodes represent the components of the product and the links represent the interfaces between the components can be show in this software. Part count reduction through part combination is a recognized goal of design for assembly (DFA). The benefits of part count reduction are: a reduced the number of assembly operations, reduced procurement costs, cycle time reduction, supply chain reduction, and higher potential profits. In this software, if the interaction between two components has been show and can combine if the interaction between components follows relation motion guideline. The selected case study of can opener has been selected by using this software and for pen and nail clipper is selected for comparison between this software and DFMA software. From comparison between this software and DFMA software has prove that the efficiency is closed different and this software is valid in terms of its result.